2020
DOI: 10.1159/000510641
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Polymorphisms in the <b><i>IL-1</i></b> Gene and the Risk of Rheumatoid Arthritis and Systemic Lupus Erythematosus: Evidence from a Meta-Analysis

Abstract: <b><i>Background:</i></b> Previous studies on polymorphisms in interleukin-1 (<i>IL-1</i>) and the risk of rheumatoid arthritis (RA)/systemic lupus erythematosus (SLE) yielded inconsistent results. <b><i>Objectives:</i></b> The authors performed this meta-analysis to more robustly evaluate associations between polymorphisms in the <i>IL-1</i> gene and the risk of RA/SLE. <b><i>Methods:</i></b> MEDLINE, Embase, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…Furthermore, an ethnicity-specific meta-analysis suggested that the IL-1B −511 C/T polymorphism was associated with RA susceptibility in Caucasians, whereas the IL-1B +3953 C/T polymorphism was associated with susceptibility to RA in Caucasian and in Asian populations [17]. Other studies found that IL-1B +3954 polymorphism was significantly associated with the risk of RA in the overall population and in Asian people [18,19]. Furthermore, an analysis conducted in the Japanese population revealed that individuals affected with both RA and periodontitis may display different distributions of IL-1B +3954 genotypes than healthy controls and subjects with periodontitis only [20].…”
Section: Il-1β the Badmentioning
confidence: 99%
“…Furthermore, an ethnicity-specific meta-analysis suggested that the IL-1B −511 C/T polymorphism was associated with RA susceptibility in Caucasians, whereas the IL-1B +3953 C/T polymorphism was associated with susceptibility to RA in Caucasian and in Asian populations [17]. Other studies found that IL-1B +3954 polymorphism was significantly associated with the risk of RA in the overall population and in Asian people [18,19]. Furthermore, an analysis conducted in the Japanese population revealed that individuals affected with both RA and periodontitis may display different distributions of IL-1B +3954 genotypes than healthy controls and subjects with periodontitis only [20].…”
Section: Il-1β the Badmentioning
confidence: 99%
“…Zhu et al (12) , concluyen que tres variantes polimórficas asociadas a la interleucina 1 (IL-1) tienen relación con LES, esta es una citocina de tipo proinflamatoria que se conoce tiene implicación en la iniciación y desarrollo de enfermedades autoinmunes conllevando a un estado proinflamatorio, sin embargo, sugieren más estudios para validación. Por su parte Zhu X et al (26) determinaron que el SNP de la interleucina 33 (IL-33), un nuevo tipo de interleucina considerada parte de la familia de IL-1, aumenta el riesgo de LES al inducir inflamación crónica, además establecieron que el tabaquismo tiene un papel de interacción considerable al incrementar el riesgo de la enfermedad.…”
Section: Lupus Eritematoso Sistémicounclassified
“…(7) La autoinmunidad se encuentra estrictamente asociada a alteraciones genéticas responsables de la pérdida de tolerancia y el desarrollo de autoanticuerpos, (8) teniendo una mayor predisposición de heredabilidad los gemelos monocigotos; estos factores genéticos promueven polimorfismos asociados al sistema de complemento, regiones del antígeno leucocitario humano, interleucinas, proteínas del tipo tirosina fosfatasa, lectina de unión a manosa, afección de nucleótidos simples, entre otras. (8,9,10,11,12) El objetivo de este estudio es determinar los polimorfismos genéticos predisponentes al desarrollo de lupus eritematoso sistémico a través de una revisión bibliográfica.…”
Section: Introductionunclassified
“…Furthermore, the neuronal type I IL-1 receptor (nIL-1R1) can utilize different coreceptors for signal transduction, IL-1 excites neurons without activating the transcription of inflammatory cytokines in the nuclear factor kappa B (NF-κB) pathway [ 59 ]. Studies have also shown that IL-1A + polymorphisms may affect RA risk in the overall population, while IL-1B+ polymorphisms may affect RA risk in the general and Asian populations [ 60 ]. However, how IL-1 participates in RA pathogenesis via the CNS and potential treatments require further study.…”
Section: Cns Modulation Of Ramentioning
confidence: 99%
“…IL-1A+ polymorphisms have also been linked to an increased incidence of RA in the general population, while IL-1B+ polymorphisms may affect RA risk in the general and Asian populations [ 60 ]. However, how IL-1 participates in RA pathogenesis via the CNS and potential treatments require further study [ 54 ].…”
Section: Cns Modulation Of Ramentioning
confidence: 99%